Hubungan Mahasiswa Dalam Organisasi Terhadap Akademik Mahasiswa - Aulia, Dinda; Muliani, Amelia Sri; Natasha, Ficha (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to examine the relationship between students' involvement in organizations and their academic performance. The research focuses on understanding the role of organizations in influencing students' academic achievements. The approach used is quantitative research with a descriptive research design. Data collection is conducted through the distribution of questionnaires to students actively involved in organizations. The results of this research are expected to provide insights into the extent to which involvement in organizations can impact students' academic aspects.